Do we need to conduct full-thickness closure after endoscopic full-thickness resection of gastric submucosal tumors? - Li, Yandong; Cui, Zhao; Yu, Jiangping; Bao, Xiaoyan; Wang, Shi (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Successful closure of gastric wall defects is a pivotal step for endoscopic full-thickness resection (EFTR). Our study indicates that for submucosal tumors (SMTs) smaller than 2.5 cm, closing the mucosal layer is safe and feasible when the modified method, ZIP, is used.Materials and Methods: We retrospectively analyzed 37 patients with gastric SMTs arising from the muscularis propria (MP) underwent EFTR with defect closure of the mucosal layer. The main procedure involved (1) making a longitudinal incision of the mucosal and submucosal layers above the lesion; (2) fully exposing the lesion and symmetrically punching holes on both sides of the incision into the submucosal layer; (3) en bloc resection of the lesion using an electrosurgical snare or knife; (4) hooking of metallic clips into the holes and clipping of the mucosal layer successively to close the gastric wall defect. We name this modified method ZIP.Results: Successful complete resection by EFTR was achieved in 37 cases (100%). The median procedure time was 60 min (range 30-120 min), while the closure procedure took a median of 8 min (range 5-20 min). The median lesion size was 1.0 cm (range 0.5-2.5 cm). No patients had severe complications. No residual lesions or tumor recurrence were found during the follow-up period.Conclusion: Closing the mucosal layer of gastric wall defects after EFTR by ZIP is feasible and effective.